Dynamic behaviour of single storied box-type masonry buildings with and without roof slab and shock table studies on scaled building models - Sivaraja, S. Saileysh; Thandavamoorthy, T.S. (Journal of Structural Engineering, 2024)
The code of practice for brick masonry IS: 4326 (1993) suggests the use of lintel band to integrate the structure and thus introduce a rigid box like behaviour. Though the code recommendations are based on the experiments carried out elsewhere, the problem is still a complex one because each type of building is unique in construction features like different ratio of binder to sand used in mortar, thickness of mortar and provision of openings etc. In the research works carried out in the past on brick masonry a number of contributions to strength and stiffness have been made. So far, the effect of slab has not considered in these researches. Here, in an attempt has been made to study the un-reinforced masonry (URM) with roof slab as an integral system. This investigation consisted of a series of experiments. The following aspects such as characteristics of bricks and URM, Natural Frequencies of single storied box-type masonry buildings with and without roof slab have been studied and presented in detail. The Shock Table studies on 1/3ʳᵈ building model was performed to investigate the base shock resistance and failure patterns of the model with and without roof slab. In this process the base acceleration of the model along with its energy absorption capacity for each impact have been investigated. The fundamental frequency of model without slab was 5.23 Hz and that with slab was 11.02 Hz. The models failed under fundamental mode of vibration and subsequently there was progressive failure of the models. Excessive cracking, buckling of wall, falling down of wall, etc, have been observed as failure modes of model. It was observed that the total energy imparted to the masonry element size of 2.10 m × 1.10 m × 0.092 m without roof slab was 4,304.10 Nm at 23ʳᵈ impact, with roof slab was 6,309.92 Nm at 34ᵗʰ impact and with slab with moment resisting frame (MRF) was 10,032.72 at 38ᵗʰ impact.